Nanomedicine and Nanobiotechnology - Logothetidis, Stergios; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book presents the laboratory, scientific and clinical aspects of nanomaterials used for medical applications in the fields of regenerative medicine, dentistry and pharmacy. It gives a broad overview on the in vitro compatibility assessment of nanostructured materials implemented in the medical field by the combination of classical biological protocols and advanced non-destructive nano-precision techniques with special emphasis on the topographical, surface energy, optical and electrical properties. Materials in the physical form of nanoparticles, nanotubes, and thin films are addressed in terms of their toxicity. The different pillars of the Nanomedicine field are also highlighted. The book takes an interdisciplinary approach of medicine, biology, pharmacy, physics, chemistry, engineering, nanotechnology and materials science. The international group of authors specifically chosen for their distinguished expertise belong to the academic and industrial world in order to provide a broader perspective. It appeals to researchers and graduate students.
Nanotechnology and medical applications -- Nanomedicine pillars and monitoring nano-bio interactions -- In-vitro testing of thin films -- Biofunctionalization of surfaces with peptides, proteins or sub cellular organelles: single molecule studies and nanomedical approach -- Imaging the human body: micro- and nanostructure of human tissues -- Nanodentistry -- Immune toxicity of nanomedicines -- Imaging of the brain with nanoparticles -- Pharmacogenomics and nanotechnology towards advancing personalized medicine.
Keywords: Physics; Pharmaceutical technology; Dentistry; Engineering; Biomaterials; Physics; Nanoscale Science and Technology; Biophysics and Biological Physics; Biomaterials; Dentistry; Nanotechnology and Microengineering; Pharmaceutical Sciences/Technology.